2012
DOI: 10.1093/heapol/czs096
|View full text |Cite
|
Sign up to set email alerts
|

From reaching every district to reaching every community: analysis and response to the challenge of equity in immunization in Cambodia

Abstract: Background An international review of the Cambodian Expanded Programme on Immunization (EPI) in 2010 and other data show that despite immunization coverage increases and vaccine preventable diseases incidence reductions, inequities in access to immunization services exist. Utilizing immunization and health systems literature, analysis of global health databases and the EPI review findings, this paper examines the characteristics of immunization access and outcome inequities, and describes proposed longer-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…In line with our results, a study from Cambodia showed that socioeconomic factors were most strongly associated with decreased access to immunization services, compared to other factors such as gender or rural/urban location 23 . Furthermore, social distance, that is the distance a person is from health care in terms of acceptability and affordability, was discussed as the main determinant of immunization access as compared to geographical distance 23 . Our study confirms that geographical location, or the urban/rural divide, does not contribute to differences in immunization coverage.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our results, a study from Cambodia showed that socioeconomic factors were most strongly associated with decreased access to immunization services, compared to other factors such as gender or rural/urban location 23 . Furthermore, social distance, that is the distance a person is from health care in terms of acceptability and affordability, was discussed as the main determinant of immunization access as compared to geographical distance 23 . Our study confirms that geographical location, or the urban/rural divide, does not contribute to differences in immunization coverage.…”
Section: Discussionsupporting
confidence: 91%
“…Use of immunization campaigns and 'outreach' strategies that target under-covered population groups is one such approach. This includes the Reaching Every District (RED) micro-planning process strategy developed in 2002 by the WHO, UNICEF and other partners, and successfully used in Africa, India, and other Asian countries [46][47][48][49]. Supplementary Immunization Activities (SIAs), also referred to as mass-immunization campaigns, employed to improve protection at population levels via increased coverage, or to achieve global elimination goals or contain outbreaks, have also shown value in reducing inequity within populations [1,[50][51][52].…”
Section: Reducing Within-country Inequities In Access To Immunizationmentioning
confidence: 99%
“…RED districts receiving training and support from an immunization consultant did not reach better coverage than comparison districts without this support but obtained improvements in the quality of the program. Cambodia [46] Analysis of the social determinants of non-access to immunization and shift of "Reach Every District" to "Reach Every Community" Cholera vaccination, Zanzibar [52] Evaluation of social and cultural factors and of barriers to understand reasons for a coverage of 50% despite 94% of the adult population willing to receive free oral cholera vaccines. Campaigns should be announced at least a few months before vaccination posts open, with repeated reminders in the target communities, consider an extension of daily open hours or numbers of days for the vaccination especially in rural areas.…”
Section: Implementation Researchmentioning
confidence: 99%
“…Most studies in low-income countries highlight the role of maternal education and knowledge on the use of immunization services [24][25][26][27][28][29][30][31][32][33][34][35]. In these studies, lower coverage was associated with lower education and knowledge levels of mothers.…”
Section: Factors Affecting Vaccination Coveragementioning
confidence: 99%
“…Bishai et al [24] found a positive association between socioeconomic status and immunization coverage in Bangladesh. Similarly, in Cambodia, socioeconomic status and ethnicity affected coverage rates [31]. Cutts et al [27] found that mother's employment was positively associated with completion of vaccination services in Guinea.…”
Section: Factors Affecting Vaccination Coveragementioning
confidence: 99%